Extensive or partial first rib resection for thoracic outlet syndrome? The contribution of three‐dimensional imaging to the preoperative planning and the postoperative evaluation. Issue 8 (5th June 2018) - Spartalis, Eleftherios; Spartalis, Michael; Tsilimigras, Diamantis I.; Moris, Demetrios; Garmpis, Nikolaos; Damaskos, Christos; Dimitroulis, Dimitrios; Troupis, Theodore; Tomos, Periklis
Key Clinical Message: Transaxillary partial excision of the first rib is associated with minimal morbidity and excellent relief of symptoms of thoracic outlet syndrome due to instant and permanent obviation of the external arterial compression. Three‐dimensional imaging offers incremental value of the surgical outcome, highlighting the role of minimally invasive partial resection. Abstract : Transaxillary partial excision of the first rib is associated with minimal morbidity and excellent relief of symptoms of thoracic outlet syndrome due to instant and permanent obviation of the external arterial compression. Three‐dimensional imaging offers incremental value of the surgical outcome, highlighting the role of minimally invasive partial resection.